1999
DOI: 10.1016/s0092-8674(00)80557-7
|View full text |Cite
|
Sign up to set email alerts
|

Germ Cells

Abstract: Germ Cells Reviewand localized to the posterior cytoplasm by a microtu-Chris Wylie bule (and possibly actin)-based mechanism during oo-Department of Pediatrics genesis. Extensive genetic screens have identified a Developmental Genetics Center large number of maternal effect genes required for germ University of Minnesota School of Medicine cell formation (see Table 1). Several of these (gurken, Minneapolis, Minnesota 55455 torpedo, Notch, Delta) are required for correct anteriorposterior patterning of the oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
182
0
6

Year Published

1999
1999
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(188 citation statements)
references
References 112 publications
0
182
0
6
Order By: Relevance
“…However, the size and location of this body correspond to the yolk nucleus, a tight aggregate of membranes and vesicles within Balbiani's vitelline body, a poorly understood cytoplasmic complex (including a dense cloud of mitochondria, lamellar aggregates, and electrondense material) encompassing most of the ooplasm in species ranging from spiders to humans (22,32). The electron-dense material, which is intimately associated with and typically surrounds the yolk nucleus, corresponds to nuage, which in many species is asymmetrically distributed during embryogenesis and appears to play a determinative role in germ cell formation, whereby cells that inherit germ plasm are destined to become germ cells (1,2). A structure analogous to the yolk nucleus, termed the sponge body, has been described recently in Drosophila, and proposed to be involved in the assembly and transport of mRNAs such as bicoid in oocytes (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the size and location of this body correspond to the yolk nucleus, a tight aggregate of membranes and vesicles within Balbiani's vitelline body, a poorly understood cytoplasmic complex (including a dense cloud of mitochondria, lamellar aggregates, and electrondense material) encompassing most of the ooplasm in species ranging from spiders to humans (22,32). The electron-dense material, which is intimately associated with and typically surrounds the yolk nucleus, corresponds to nuage, which in many species is asymmetrically distributed during embryogenesis and appears to play a determinative role in germ cell formation, whereby cells that inherit germ plasm are destined to become germ cells (1,2). A structure analogous to the yolk nucleus, termed the sponge body, has been described recently in Drosophila, and proposed to be involved in the assembly and transport of mRNAs such as bicoid in oocytes (33).…”
Section: Discussionmentioning
confidence: 99%
“…Although high levels of conservation exists in body plan and axis formation across species, germ cell fate specification in mammals (at least in mice) appears to be unique in which maternally derived factors have not been shown to play any roles (1)(2)(3). Consistent with data of embryological studies that extraembryonic ectoderm signals the proximal epiblast to develop toward a PGC fate, genetic studies have revealed that BMP4 and BMP8B serve as the extraembryonic ectoderm-derived factors to induce PGCs (6-8, 19, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal factors play critical roles in germ cell specification in Drosophila, Caenorhabditis elegans, zebrafish, and frogs (1)(2)(3)(4)(5). By contrast, mice appear to use rather different developmental mechanisms.…”
mentioning
confidence: 99%
“…The precursors of the gametes are known as primordial germ cells (PGCs), and are morphologically similar in males and females. PGCs migrate from the hindgut endoderm to the mesoderm of the urogenital ridges to be incorporated into the future gonads (for review, see Wylie, 1999 Cell-cell interactions are known to be required for germ cell survival in embryonic and adult mice (Nocka et ah, 1989). Mouse PGCs will not migrate on plastic or purified extracellular matrix proteins, but will migrate on fibroblast feeder layers (Donovan et ah, 1986).…”
Section: Introductionmentioning
confidence: 99%